Calculation of interlock, 1 × 1 rib, and single jersey knitted fabrics shrinkage during the dyeing process after determining loop shape. Issue 21 (November 2021) - Llinares Berenguer, Jorge; Díaz-García, Pablo; Miró Martinez, Pau
This study investigated existing dimensional variations in knitted fabrics produced by weft-knitting technology for knitting and dry relaxation, dyed and dry relaxation, and dyed and wash relaxation for the interlock, 1 × 1 rib, and single jersey structures. This paper demonstrates that once the structure has been knitted, the shape that the loop takes in the fabric, and loop length and loop width, for each relaxation state will be the main factor responsible for dimensional variations in cotton knitted fabrics. It also shows how loop length affects knitted fabric dimensions when knitting machine parameters are modified by varying the use of feeders, and obtaining more loosely or more tightly knitted fabrics. In this study a model to predict the longitudinal and transversal shrinkage of interlock, 1 × 1 rib, and single jersey fabrics after the dyeing process is presented. This avoids following the conventional analysis procedure according to Standard UNE-EN ISO 6330 of September 2012 and, thus, avoids investing relatively long calculation times, which speeds up the production process by avoiding product lots being stopped. These results are important for textile industry technicians as they substantially simplify production calculations in weft-knitted fabrics companies. This work offers an effective method for predicting the longitudinal and transversal shrinkage and width of knitting fabrics after the dyeing process from the loop dimension after the knitting process. The application of the study results may help businesses to significantly save time and, consequently, imply an intermediate product stock investment saving.